2019
DOI: 10.1101/548909
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Critical Nodes of Virus–Host Interaction Revealed Through an Integrated Network Analysis

Abstract: Viruses are one of the major causes of various acute and chronic infectious diseases and thus a major contributor to the global burden of disease. Several studies have shown how viruses have evolved to hijack basic cellular pathways and evade innate immune response by modulating key host factors and signalling pathways. A collective view of these multiple studies could advance our understanding of viral evasion mechanisms and provide new therapeutic perspectives for the treatment of viral diseases. Here, we pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 89 publications
2
8
0
Order By: Relevance
“…Experimental studies have shown that azacitidine is a potent, broadspectrum antiviral agent. The range of viruses against which it shows activity includes AdV (Alexeeva et al, 2001(Alexeeva et al, , 2015, human metapneumovirus (HMPV) (Bösl et al, 2019), HIV-1 (Dapp et al, 2009;Rawson et al, 2016a), HIV-2 (Beach et al, 2014), Rift Valley fever virus (RVFV) (Ianevski et al, 2018, human T-lymphotropic virus (HTLV-1) (Diamantopoulos et al, 2012), HSV-1, and FLUAV (Ianevski et al, 2018). A study of azacytidine activity against HIV-1 and HIV-2 revealed that it primarily targets reverse transcription (in the form of 5azacytidine-triphosphate or 5-aza-2′-deoxycytidine triphosphate).…”
Section: Nucleoside Antimetabolites -Approved Antineoplastic Drugs Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have shown that azacitidine is a potent, broadspectrum antiviral agent. The range of viruses against which it shows activity includes AdV (Alexeeva et al, 2001(Alexeeva et al, , 2015, human metapneumovirus (HMPV) (Bösl et al, 2019), HIV-1 (Dapp et al, 2009;Rawson et al, 2016a), HIV-2 (Beach et al, 2014), Rift Valley fever virus (RVFV) (Ianevski et al, 2018, human T-lymphotropic virus (HTLV-1) (Diamantopoulos et al, 2012), HSV-1, and FLUAV (Ianevski et al, 2018). A study of azacytidine activity against HIV-1 and HIV-2 revealed that it primarily targets reverse transcription (in the form of 5azacytidine-triphosphate or 5-aza-2′-deoxycytidine triphosphate).…”
Section: Nucleoside Antimetabolites -Approved Antineoplastic Drugs Wimentioning
confidence: 99%
“…Myelodysplastic syndrome (2004) AdV (Alexeeva et al (2001); (Alexeeva et al, 2015) HMPV (Bösl et al, 2019) HIV-1 (Dapp et al, 2009;Rawson et al, 2016a) HIV-1 -synergy in combination with resveratrol (Rawson et al, 2016b) HIV-2 (Beach et al, 2014) RVFV ( (Clouser et al, 2012) HIV-1 -synergy in combination with decitabine (Clouser et al, 2010) MuLV (Clouser et al, 2012) HIV-2 (Beach et al, 2014) ZIKV (Kuivanen et al, 2017) Enteroviruses including poliovirus (Kang et al, 2015;Zhang et al, 2017) Enteroviruses -synergy with ribavirin (Kang et al, 2015) Rhinoviruses (Song et al, 2017) HCV (Beran et al, 2012) Coronaviruses (Dyall et al, 2014) SINV, HSV-1, FLUAV (Denisova et al, 2012) Gram-positive bacteria (Jordheim et al, 2012;Sandrini et al, 2007;…”
Section: Introductionmentioning
confidence: 99%
“…Other cell death assays include LDH enzyme leakage assays, membrane impermeable dye-based assays, and apoptosis assays, such as Annexin V, TUNEL, and caspase assays (19). For example, the Cell Titer Glo (CTG) assay quantifies ATP, an indicator of metabolically active living cells, whereas Cell Tox Green assay uses fluorescent asymmetric cyanine dye that stains the DNA of dead cells (13,(20)(21)(22).…”
Section: Discovery Of Novel Bsaa Activities In Immortalized Cell Cultmentioning
confidence: 99%
“…For example, TZM-bl cells expressing firefly luciferase under control of HIV-1 LTR promoter allowed quantitation of BSAA action on HIV-1 infection (tat-protein expression by integrated HIV-1 provirus) using firefly luciferase assay (23,24). RFP-expressing RVFV, nanoLucexpressing CHIKV and RRV, as well as GFP-expressing FLUAV, HCV and HMPV also allowed identification of novel activities of several BSAAs (13,21,(25)(26)(27)(28)(29)(30)(31). In addition, qPCR/RT-qPCR, RNA/DNA sequencing, RNA/DNA hybridization, immuno-and plaque assays as well as CRISPR-CAS9 systems could be used for detection of inhibitory effects of BSAAs (32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Discovery Of Novel Bsaa Activities In Immortalized Cell Cultmentioning
confidence: 99%
See 1 more Smart Citation